Advanced Techniques for Resource Allocation and Routing in SDM-EONs - Oliveira, Ramon A.; Rosário, Denis L.; Oliveira, Helder M. N. S. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2026: Anais Estendidos do XLIV Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2026.19689, 2026)
The rapid growth in the number of Internet users, connected devices, and data-intensive services is pushing current optical network infrastructures to their limits, creating a demand for scalable, adaptive, and high-capacity solutions. Elastic Optical Networks (EONs) and space-division multiplexing (SDM) technologies have emerged as promising alternatives to traditional WDM systems, offering improved flexibility and capacity at the cost of increased network management complexity and physical-layer impairments. In this context, SDM-enabled Elastic Optical Networks (SDM-EONs) introduce challenging Routing, Modulation, Spectrum, and Space Allocation (RMSSA) problems. This work proposes the SimpleSimSDM simulation platform and a set of novel RMSSA approaches for SDM-EONs. Two space and spectrum allocation policies, CAD-BA and PAPAA, are introduced to balance bandwidth blocking, crosstalk, and fragmentation, while a routing strategy, MCC-FT, leverages multiple degradation metrics to reduce bandwidth blocking caused by localized node saturation.